Evaluación del proceso de extracción de la enzima lactasa a partir de kluyveromyces marxianus para aprovechamiento de residuos agroindustriales - León Acosta, Steven André (2019)
Kluyveromyces marxianus is a yeast that has application in the field of agribusiness, mainly for its ability to synthesize the enzyme B-galactosidase, which is responsible for the breakdown of the lactose molecule into glucose and galactose molecules. The purpose of this research was to evaluate the extraction process of lactase enzyme from Kluyveromyces marxianus. The yeast strain LAF-4 CHR Hansen was tested in different culture media, that used whey discarded from the dairy industry as its main component. For this purpose, different chemical compositions of the culture medium were evaluated, which were based on the use of whey. The variable under analysis was the growth rate. Once the Analysis of Variance (ANOVA) and subsequent Functional Analysis of the results with significant difference was performed, the optimum conditions to which Kluyveromyces marxianus generates the greatest amount of biomass was determined, which corresponds a pH of 6.5 and 100 percent of whey concentration, selecting the treatment T9 as the one that obtained the best results: with a biomass generation equivalent to 608.43 mg / ml for 24 hours and with a growth rate of 25.35 mg / h. Finally, the extraction of the enzyme produced under the conditions corresponding to treatment T9 was carried out by sonication. The enzymatic activity was evaluated through an indirect method with a glucometer, where the extracted enzyme was added in to a milk sample in a dose of 0.8 g / L, after 40 minutes of maintaining a temperature of 50 degrees Celsius, the end of the hydrolysis was evidenced, since the glucose levels got stabilized.